2014
DOI: 10.1080/10610278.2013.860226
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-promoted energy transfer for broadly applicable small-molecule detection

Abstract: Reported herein is the development of non-covalent, proximity-induced energy transfer from small-molecule toxicants to organic fluorophores bound in the cavity of γ-cyclodextrin. This energy transfer occurs with exceptional efficiency for a broad range of toxicants in complex biological media, and is largely independent of the spectral overlap between the donor and acceptor. This generally applicable phenomenon has significant potential in the development of new turn-on detection schemes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 63 publications
(56 reference statements)
0
27
0
Order By: Relevance
“…Similarly, methyl-β-cyclodextrin was most efficient at extracting fluorophore 4 from the oil layer into a cyclodextrin-containing seawater solution ( Figure 4) for both oil spill oil and tar ball oil samples. This fluorophore has been used previously by our group as a highly efficient fluorescent acceptor in cyclodextrin-promoted energy transfer schemes [12][13][14][15][16], and results using this fluorophore have been shown to be virtually indistinguishable from results obtained with a less functionalized BODIPY acceptor [see ESI for ref. 14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, methyl-β-cyclodextrin was most efficient at extracting fluorophore 4 from the oil layer into a cyclodextrin-containing seawater solution ( Figure 4) for both oil spill oil and tar ball oil samples. This fluorophore has been used previously by our group as a highly efficient fluorescent acceptor in cyclodextrin-promoted energy transfer schemes [12][13][14][15][16], and results using this fluorophore have been shown to be virtually indistinguishable from results obtained with a less functionalized BODIPY acceptor [see ESI for ref. 14].…”
Section: Resultsmentioning
confidence: 99%
“…This system operates successfully to extract PAHs from motor oil, vacuum pump oil, and vegetable oil, as well as from oil collected from oil spill sites and from tar balls [9]. The most efficient cyclodextrin hosts were found to be either γ-cyclodextrin, which is well-known to form ternary complexes [10,11] and promote proximity-induced energy transfer [12][13][14][15] or 2-hydroxypropyl-β-cyclodextrin (2-HPCD) [16], which was substantially more efficient at extracting the PAHs compared to γ-cyclodextrin, although somewhat less efficient at promoting PAH-to-fluorophore energy transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The most likely explanation for this scenario is that cyclodextrins facilitate the association of the aromatic toxicants with fluorophore 4. This facilitated association can either occur via the formation of a ternary complex in the cyclodextrin cavity (as has been demonstrated for γ -cyclodextrin [20][21][22]44,45 and 2-HPCD 46 , 47 ), or via association of one of the two energy transfer partners outside the cyclodextrin cavity (a more likely scenario for the smaller cyclodextrin derivatives).…”
Section: Materials Andmentioning
confidence: 99%
“…[19][20][21][22] Other research groups have also reported the use of cyclodextrin derivatives to extract PAHs from complex environments, including from contaminated soil 23,24 and river sediments. 25 Previous research in our group focused on the use of γ -cyclodextrin for the extraction and detection of PAHs from motor oil, vegetable oil, and vacuum pump oil.…”
mentioning
confidence: 99%
“…13 In these detection schemes, cyclodextrin promotes highly efficient energy transfer from a small molecule analyte to a high quantum yield fluorophore, resulting in a bright turnon fluorescence signal in the presence of the target analyte ( Figure 1). This energy transfer scheme has been used successfully in complex systems such as biological fluids 14 and crude oil collected in the aftermath of an oil spill. 15 It has been used in the development of array-based detection schemes, 16 and as part of tandem extraction-detection-detoxification environmental remediation schemes for environmental remediation efforts.…”
Section: Rapid and Efficient Pesticide Detection Via Cyclodextrinprommentioning
confidence: 99%